Small-scale food processing in Mozambique, South Africa and Zambia: addressing INFORMATION MANAGEMENT needs for sector development - Atkinson, Keith; Cardoso, Maria Jose; Hill, Nora (Technical Centre for Agricultural and Rural Cooperation, 2000)
The report highlights the potential contribution of small-scale food enterprises to the economies of these countries, and discusses the constraints such enterprises face, including poor access to finance and unfavourable environments.